2014
DOI: 10.4293/108680813x13693422518317
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Port-Site Incisional Hernia After Single-Incision Laparoscopic Surgery

Abstract: Background and Objectives:Single-incision laparoscopic surgery is gaining popularity among minimally invasive surgeons and is now being applied to a broad number of surgical procedures. Although this technique uses only 1 port, the diameter of the incision is larger than in standard laparoscopic surgery. The long-term incidence of port-site hernias after single-incision laparoscopic surgery has yet to be determined.Methods:All patients who underwent a single-incision laparoscopic surgical procedure from May 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 27 publications
0
44
0
3
Order By: Relevance
“…It has been argued against single port laparoscopy that there could be a higher rate of incisional hernia. [26][27][28][29][30][31] We did not find any such difference, and we actually believe that it is easier to close the fascial wound after single port laparoscopy because the larger skin incision facilitates the closing. Longer follow-up time should in any case be employed to re-evaluate whether incisional hernia rates continue to be equal in both groups.…”
Section: Discussionmentioning
confidence: 65%
“…It has been argued against single port laparoscopy that there could be a higher rate of incisional hernia. [26][27][28][29][30][31] We did not find any such difference, and we actually believe that it is easier to close the fascial wound after single port laparoscopy because the larger skin incision facilitates the closing. Longer follow-up time should in any case be employed to re-evaluate whether incisional hernia rates continue to be equal in both groups.…”
Section: Discussionmentioning
confidence: 65%
“…4 Some authors indicated that they believe that because of the substantially thickened preperitoneal space and increased intra-abdominal pressure, there is a tendency to improperly close the fascial defect in obese patients. 9 The majority of studies did not assess the effect of body mass index (BMI) on the incidence of PSH. One study suggested that there may be a correlation with sudden weight gain and hernia development following surgery rather than obesity itself.…”
Section: Discussionmentioning
confidence: 99%
“…One study suggested that there may be a correlation with sudden weight gain and hernia development following surgery rather than obesity itself. 9 Other patient related factors which increased risk of PSH are diabetes mellitus, chronic obstructive pulmonary disease, arterial insufficiency, immune deficiency, malnutrition, smoking and infection (usually present with late onset type PSH) at incision site. 4,9 Trocar diameter has been widely reported as a factor in development of PSH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the laparoscopic literature, reported rates range between 2.9 and 8.4% [17,56]. Data from robotic single-site surgery are limited to smaller case series.…”
Section: Herniamentioning
confidence: 99%